ON PUBLIC ORGANIZATIONS AT THE DON AND THE NORTH CAUCASUS IN THE SECOND HALF OF THE XIX - BEGINNING OF THE XX CENTURY - Elena Luybyshkina (Гуманитарные и юридические исследования)
The article deals with the types and forms of work of public organizations in the Don and the North Caucasus in the second half of the XIX - early XX centuries. Based on the characteristics of the region under consideration, due to the special multicultural environment that distinguishes the Don and the North Caucasus from other territories that have no analogues in Russia, regional public organizations are represented by branches of all-Russian societies, directly regional self-organizing societies and associations that reflect the intraregional specificity. Public organizations in the Don and the North Caucasus were created in line with the all-Russian process of development of civil associations. The article shows that there were both wide-profile public organizations, combining different forms of work and types of assistance, and narrowly targeted public organizations in the Don and the North Caucasus. The activity of agricultural public organizations, educational, scientific and intellectual, health, national, charitable, cultural, aesthetic, moral and educational societies for the improvement of villages and cities is considered. The work of agricultural societies was important in the process of deepening the specialization of agricultural production in the region: gardening and vine-growing associations, societies for the development of beekeeping and horse breeding. The activities of educational societies were aimed at overcoming the problems of illiteracy and providing various forms of assistance in expanding access to education, to the establishment of schools, libraries, Sunday schools, evening courses, conducting lecture campaigns and public readings. Charitable public organizations conducted work on the establishment of charitable undertakings, payment of benefits, assistance in education and health, employment management. The qualitative indicators of the work of public organizations affecting a wide range of problems allows the author to speak about the active civic stance of members of voluntary public associations.